In-depth investigation of microRNA-mediated cross-kingdom regulation between Asian honey bee and microsporidian - Fan, Xiaoxue; Zhang, Wende; Zhang, Kaiyao; Zhang, Jiaxin; Long, Qi; Wu, Ying; Zhang, Kuihao; Zhu, Leran; Chen, Dafu; Guo, Rui (Frontiers in Microbiology, 2022)
Asian honey bee Apis cerana is the original host for Nosema ceranae, a unicellular fungal parasite that causes bee nosemosis throughout the world. Currently, interaction between A. cerana and N. ceranae is largely unknown. We previously prepared A. c. cerana workers’ midguts at 7 days post inoculation (dpi) and 10 dpi with N. ceranae spores as well as corresponding un-inoculated workers’ midguts, followed by cDNA library construction and a combination of RNAs-seq and small RNA-seq. Meanwhile, we previously prepared N. ceranae clean spores, which were subjected to cDNA library construction and deep sequencing. Here, based on the gained high-quality transcriptome datasets, N. ceranae differentially expressed mRNAs (DEmiRNAs) targeted by host DEmiRNAs, and host DEmRNAs targeted by N. ceranae DEmiRNAs were deeply investigated, with a focus on targets involved in N. ceranae glycolysis/glyconeogenesis as well as virulence factors, and host energy metabolism and immune response. In A. c. cerana worker’s midguts at 7 (10) dpi (days post inoculation), eight (seven) up-regulated and six (two) down-regulated miRNAs targeted 97 (44) down-regulated and 60 (15) up-regulated microsporidian mRNAs, respectively. Additionally, miR-60-y and miR-676-y in host midgut at 7 dpi could target genes engaged in microsporidian spore wall protein and glycolysis/gluconeogenesis, indicating potential host miRNA-mediated regulation of microsporidian virulence factor and energy metabolism. Meanwhile, in microsporidian at 7 (10) dpi, 121 (110) up-regulated and 112 (104) down-regulated miRNAs were found to respectively target 343 (247) down-regulated and 138 (110) down-regulated mRNAs in host workers’ midguts. These targets in host were relevant to several crucial pathways, indicative of the involvement of microsporidian DEmiRNAs in regulating these cellular and humoral immune . Meanwhile, microsporidian miR-21-x was up-regulated at 7 dpi and had a target relative to oxidative phosphorylation, suggesting that miR-21-x may be used as a weapon to modulate this pivotal energy metabolism pathway. Furthermore, potential targeting relationships between two pairs of host DEmiRNAs-microsporidian DEmRNAs and two pairs of microsporidian DEmiRNAs-host DEmRNAs were validated using RT-qPCR. Our findings lay a foundation for exploring the molecular mechanism underlying cross-kingdom regulation between A. c. cerana workers and N. ceranae, and offer valuable insights into Asian honey bee-microsporidian interaction.